Prevalence of hypertension and associated factors in people living with HIV at Senkatana Clinic Maseru - Mosa S.M. Selebalo; Benjamin J. Bryden; David M. Thompson; Jill E. Sanders (African Journal of Primary Health Care & Family Medicine, 2025)
Background: Cardiovascular diseases (CVDs), including hypertension (HTN), have emerged among people living with HIV (PLHIV) as the most important prevalent contributors of non-AIDS-related mortality. Moreover, HTN itself is a modifiable risk factor for other CVDs. Data are limited regarding the prevalence of HTN and associated factors among PLHIV in Lesotho.